Neighborhood influences on young Children's conduct problems and pro-social behavior: Evidence from an Australian national Sample [Abstract]. - Bromfield, Leah M; Edwards, Benjamin (My University, 2009)
Research into neighbourhood influences on children's outcomes shows that greater levels of neighbourhood socioeconomic disadvantage are associated with increased social, emotional and behavioural problems in children and adolescents. However, most of this research has focused on late childhood and adolescence. Using data from 'Growing Up in Australia, the Longitudinal Study of Australian Children', a nationally representative study of 4983 four-to-five-year old children growing up in 257 neighbourhoods in Australia, this article investigates the mechanisms through which neighbourhood socioeconomic status influences children's conduct problems and pro-social behaviour. After accounting for family demographic variables, children's conduct problems are found to be associated with neighbourhood socioeconomic status, neighbourhood safety and neighbourhood belonging. Perceptions of neighbourhood safety and neighbourhood belonging are found to mediate the relationships between neighbourhood socioeconomic status and children's conduct problems, and the associations of neighbourhood safety with conduct problems were mediated by neighbourhood belonging. A different pattern of results emerges for pro-social behaviour, which has direct association with neighbourhood cleanliness and neighbourhood belonging and no mediated associations.
Children and Youth Services Review
Keywords: Child Development -- Behaviour; Child Development; Childhood and child development; Child Development; Behaviour; Childhood and child development